2018
DOI: 10.1039/c7pp00299h
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived intermediates in photochemistry of an OsCl62− complex in aqueous solutions

Abstract: Two mechanisms of OsCl photolysis were studied by means of quantum chemical calculations in gas and aqueous phases. The difference between these mechanisms is in the nature of the possible Os(iv) key intermediates (KI). According to calculations, the intermediate is an OsCl complex of square pyramidal coordination geometry. The calculations do not give an opportunity to make an unambiguous choice between the triplet and quintet multiplicities of OsCl. The calculated CASSCF/IMCP-SR1 transition energies for OsCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…(2007) and Rogozina et al. (2017) showed that the stability of Os(IV)‐Cl complexes was influenced by oxygen fugacity and temperature. This study supports these findings by suggesting that the solubility of Os(IV) as well as the stability of Os species in Cl‐rich solutions is also high and could be influenced by temperature, Cl concentration, pH, and oxygen fugacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2007) and Rogozina et al. (2017) showed that the stability of Os(IV)‐Cl complexes was influenced by oxygen fugacity and temperature. This study supports these findings by suggesting that the solubility of Os(IV) as well as the stability of Os species in Cl‐rich solutions is also high and could be influenced by temperature, Cl concentration, pH, and oxygen fugacity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at temperatures above 450°C, the absence of a quantitative relationship between the logarithm of Os concentration and the logarithm of H + activity (Figure 4a) suggests a change in the Os‐Cl species in aqueous solutions. Considering the hydrolysis rule of Os cation expressed by Equation 2, Os cation in aqueous solutions at higher temperatures may exist in the form of Os‐OH‐Cl complexes, such as OsCl 5 (OH) 2− , OsCl 3 (OH) 3 2− , OsCl 2 (OH) 4 2− , or OsCl(OH) 5 2− (Rogozina et al., 2017), due to the change in the ionization of HCl. As temperature rises above 450°C, the ionization of HCl is weakened (Mei et al., 2018), which provides less Cl − to the complexation between Os and Cl ions and results in the formation of the Os‐OH‐Cl complexes other than Os‐Cl complexes through the OH − substitution to Cl − in solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that the electronic structure of [OsCl 6 ] 2À dianion has become a subject of theoretical studies numerous times, [28,[31][32][33] we started theoretical exploration from full 1). To understand the nature and quantify the strength of intermolecular non-covalent S⋅⋅⋅Cl and O⋅⋅⋅Cl interactions in the crystal structure of 1, DFT calculations for a model supramolecular associate were performed at the ωB97XD/DZP-DKH level of theory followed by the topological analysis of the electron density distribution within the QTAIM approach [34] (Table S4, see ESI).…”
Section: Theoretical Studymentioning
confidence: 99%